HUBUNGAN JENIS ALAT KONTRASEPSI DENGAN GANGGUAN KESEHATAN REPRODUKSI - Ari Sulistyawati (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2018)
Reproductive health problems experienced by women greatly influence the quality of life of women in all aspects of their roles. The prevalence of reproductive health disorders is very high, even more than 90% of women experience it. Most reproductive health disorders are associated with contraceptive use. Research on the use of contraceptives and reproductive health disorders such as vaginal discharge, menorrhagia, changes in libido, lumps in the breast, cysts, and sleep disorders is very necessary. The purpose of this study was to determine the relationship between contraceptive use and reproductive health disorders. This research is a quantitative study with a cross sectional approach. The population of women of childbearing age in Karanganom 830 hamlet, a sample of 73 people was taken through a purposive sampling method. Data obtained through questionnaires with closed questions. Univariate data were analyzed by simple descriptive and bivariate data were analyzed using Chi Square test. This study found that 60% of women experience vaginal discharge, 27% menorrhagia, 9% experience a decrease in libido, 9% experience breast lumps, 4% have cysts, and 40% experience sleep disorders, all of which use non-hormonal contraception. There is a relationship between the choice of contraceptive type with complaints of menorrhagia (p = 0.013), while for vaginal discharge, changes in libido, lumps in the breast, cysts, and sleep disorders are not related to the choice of contraception type. It is recommended to increase the resilience of a woman's body through improving patterns of activity and knowledge about reproductive health.